RIOK-2 protein is essential for egg hatching in a common parasitic nematode. Issue 8 (July 2020) - Zhou, Huan; Zhou, Taoxun; Zhang, Biying; Lei, Weiqiang; Yuan, Wang; Shan, Jianan; Zhang, Ying; Gupta, Nishith; Hu, Min
Graphical abstract: Highlights: Strongyloides stercoralis Ss-riok-2 encodes a catalytically-active kinase. Ss -RIOK-2 is located primarily in the cytoplasm of intestinal and hypodermal cells. Overexpression of a catalytically-impaired Ss- RIOK-2-D228A mutant delayed larval development. Ectopic expression of Ss -RIOK-2-K123A with a mutation in the ATP-binding site abrogated the process of egg hatching. Egg hatching could be restored by co-expressing the wild-type Ss- RIOK-2. Abstract: The atypical protein kinase RIOK-2 is a non-ribosomal factor essential for ribosome maturation in yeast and human cells; however, little is known about its physiological role in pathogens. Our earlier work examined the expression profile of a RIOK-2 gene ( Ss-riok-2 ) in Strongyloides stercoralis – a prevalent nematode parasite of dogs and humans. Herein, we demonstrate that Ss- RIOK-2 encodes a catalytically active kinase, distributed primarily in the cytoplasm of intestinal and hypodermal cells in transgenic larvae. Its expression oscillates as the free-living L1s develop into infective L3s. Overexpression of a catalytically impaired Ss- RIOK-2-D228A mutant delayed the development of transgenic larvae, while ectopic expression of another dominant negative isoform with a mutation in the ATP-binding site (K123A) abrogated the process of egg hatching, which could be rescued by co-expressing a wild-type Ss- RIOK-2 but not by its Ss- RIOK-1 ortholog. Collectively, our findings show a critical and specific role of Ss- RIOK-2 during the development of a pathogenic roundworm, which can be exploited to develop anti-infectives.